Received wisdom and beyond : lessons from fiscal consolidation in the EU - Larch, Martin; Turrini, Alessandro 1966-; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2008)
The paper examines consolidation episodes in the EU since 1970 with a view to shedding light on the factors that determine the success or failure of fiscal adjustment. Compared to the existing literature on successful fiscal consolidations we add a number of new dimensions. Three deserve particular attention. Firstly, we explore a broader set of potential ingredients of the recipe for success. In addition to the composition of adjustment, which has extensively been examined in the literature, we consider further elements such as the quality and strength of fiscal governance and the implementation of structural reforms. Secondly, our analysis seeks to differentiate between at least two different types of consolidation episodes, one in which a relatively big fiscal correction is implemented in a short period of time, dubbed 'cold shower' consolidation, as compared to more gradual episodes of adjustment. Thirdly, we check whether the 'recipe for success' changed over time. Our analysis broadly confirms the results established in the literature for what concerns (i) the conditions triggering a consolidation episode and (ii) the composition of adjustment, with minor but important qualifications related to the role played by government wages. In addition it provides evidence that well-designed fiscal governance as well as structural reforms improve the odds of both starting a consolidation episode and achieving a lasting fiscal correction. Our analysis also shows that the composition of successful and unsuccessful consolidation has become more similar over time and that other discriminating factors such as fiscal governance and structural reforms turn out to make an increasing difference for success.
Economic Papers